Teaming up and mixing methods: collaborative and cross-disciplinary work in corpus research on phraseology. Issue 1 (April 2016) - Römer, Ute
Abstract : Inspired by my positive experiences gained as a member of cross-disciplinary research teams, this paper explores the value of collaborative work in corpus linguistics. I discuss selected results from three studies that showcase research on phraseology: a study that attempts to measure formulaic language in first- and second-language writing, a study on attended/unattended this and its patterns in student writing, and a study on speaker knowledge and use of verb–argument constructions. My collaborators on these studies include a psycholinguist, a computational linguist, a cognitive linguist and a genre analysis expert. This paper highlights the ways in which combining research methods from different fields can be beneficial to research outcomes in phraseology, and calls for more collaboration between corpus linguists and scholars from neighbouring disciplines.